SUPPORT FOR STAR-0215 ADMINISTERED EVERY THREE- OR SIX-MONTHS FOR HEREDITARY ANGIOEDEMA: PHASE 1A Results - Morabito, C.; Cohen, T.; Gunsior, M.; Nichols, A.; Chung, J.; Bernard, K.; Gustafson, P.; Lumry, W. (Annals of allergy, asthma, & immunology, 2023)
STAR-0215 is an investigational extended half-life monoclonal antibody for hereditary angioedema (HAE). This trial (NCT05477160) assesses STAR-0215′s potential for safe and durable suppression of HAE attacks (≥3 months) after single doses in healthy subjects. This is a randomized, blinded, placebo-controlled, single ascending dose trial evaluating safety, tolerability, pharmacokinetics (PK), pharmacodynamics (PD), and immunogenicity of STAR-0215 after 100, 300, 600, and 1200 mg subcutaneously (SC) and 600 mg intravenously (IV) or matched placebo (3:1 randomization) in cohorts of healthy adult subjects for up to 224 days. PD is assessed by changes in cleaved high-molecular-weight-kininogen (cHMWK). This report includes complete results from the 100, 300 and 600 mg SC cohorts and initial results for the 1200 mg SC and 600 mg IV cohorts. 41 subjects received STAR-0215 (n=31) or placebo (n=10). Mild, related treatment emergent adverse events were seen in 11 subjects, most commonly injection site reactions (n=9). STAR-0215 demonstrated dose-dependent concentrations, rapid absorption, slow clearance, and median t1/2 of 87-109 days. At Day 84, median concentrations remained 1x, 3x, and 6x above 12 mcg/mL (potential efficacy threshold) after 300, 600, and 1200 mg SC, respectively. Suppression of cHMWK formation consistent with plasma kallikrein inhibition was achieved. PK modeling confirmed a range of doses administered every 3- or 6-months may be effective in HAE attack prevention (Figure). With favorable safety profile, long half-life, and durable PD, STAR-0215 demonstrates early proof of concept in healthy subjects as a potential HAE therapy with robust attack suppression and low treatment burden.